Collaborarive Administration Model For Communities Affected by Tidal Flood in Coastal Area - Edy Lisdiyono; Setiyowati; Charis Christiani; Rahmad Purwanto W; Bambang Widodo (Fakultas Hukum, Universitas Warmadewa, 2022)
Abs Rob is an event where sea air rises to inundate the surrounding land, causing environmental problems tract. This condition is the area in North Semarang City as one of the northern coastal areas of Java which is affected by tidal floods that enter villages and even enter people's houses that have not stopped for a long time, resulting in greatly disrupted activities and community access, including economic losses, damage to building facilities and infrastructure and the increasingly damaged environment. The University Service Team on 17 August 1945 Semarang has carried out socialization and assistance to communities affected by the tidal wave in the North Semarang area, especially the North Tanjung Mas Village with the Independent Learning Policy Program for the Independent Campus and received funding assistance from the Directorate General of the Ministry of Education, Research and Technology in 2021 and the results of the Service. this has been presented. The method of implementing community service is carried out by Tanjungmas Village, North Semarang District divided into two types of activities, namely: (1) Socialization activities and (2) Assistance for community groups in improving collaborative community service involving five parties (Pentahelic Approach) by involving regional officials ( in this case the Regional Disaster Management Agency, Bappeda, North Semarang District and Tanjungmas Village) as the regulator and executor of authority in the context of disaster management. There are several problems or obstacles found in the outreach and mentoring activities, namely the low capacity of human resources and the capacity of community institutions in Tanjungmas sub-district, low community involvement in tidal disaster management efforts, both individually and in institutions.